COMPARATIVE EVALUATION OF SEVOFLURANE AND ISOFLURANE IN FAST TRACK ANAESTHESIA FOR VALVULAR CARDIAC SURGERY: A RANDOMIZED STUDY - MEENA, DEEPAK KUMAR; CHARAN, PRADEEP; SHARMA, ASHA (International Journal of Current Pharmaceutical Research, 2024)
Objective: Contemporary valvular cardiac surgery has evolved with the adoption of expedited postoperative recovery, known as fast-tracking. This paradigm shift results from advancements in anaesthetic agents, surgical techniques, and myocardial protection strategies. Fast-track anaesthesia aims to reduce intensive care unit (ICU) stays and overall hospital length of stay (LOS), optimizing resource utilization. Cardioprotective properties of volatile anaesthetic agents, especially in mitigating ischemic myocardial damage, have garnered attention. Methods: A hospital-based, randomized, comparative study was conducted at the Department of Anaesthesiology, S. M. S Medical College, Jaipur. 70 undergoing valvular heart surgery under general anaesthesia, were randomly assigned to two groups: Group A (Sevoflurane) and Group B (Isoflurane). Inclusion criteria encompassed ASA grade II to IV patients aged 20 to 50 y, with a body weight of 30-65 kg, and willingness to provide written consent. Anaesthesia induction and maintenance involved the administration of Sevoflurane or Isoflurane based on group allocation. Hemodynamic parameters were recorded at various surgical stages. Results: Heart rate, systolic blood pressure, and cardiac output were statistically insignificant between groups at different surgical stages (p>0.05). Intraoperative variables demonstrated no significant differences, except for a transient decrease in systolic blood pressure post-induction in both groups. Conclusion: The study underscores the comparable efficacy of Sevoflurane and Isoflurane in valvular cardiac surgery, supported by similar hemodynamic profiles. Understanding the nuances of volatile anaesthetic agents is crucial for their optimal clinical application, considering challenges like beta-blocker usage and perioperative hyperglycemia.